Development of a Class XI Citizenship Education Learning Model Based on Blended Learning Flipped Classroom at Tunas Bangsa Vocational School, Depok - Umri Sofyan Sori; Nurdin Ibrahim; Rudi Hartono (CV. Media Inti Teknologi, 2024)
The aim of this research is to develop and test the feasibility and effectiveness of developing a Class XI Civics Education Learning Model Based on Blended Learning-Flipped Classroom at Tunas Bangsa Vocational School, Depok. This research uses the development of the Borg and Gall model which is integrated with the Rowntree model with 9 steps from the Bord and Gall model, and 3 steps from the Rowntree model. The results of the feasibility test carried out by material experts were 81%, processional design experts 94%, and media experts 88%, teacher users 87% and student users 83%. Overall, the results were in the